Improving Science Learning Outcomes on Changes in the Form of Matter Through the Media-Assisted Discovery Learning Model for Class IV Students at Sdn 8 Barru - Taufik, Nurul; Nurfadilah, Nurfadilah; Nur, A.Muafiah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This journal reviews the material on the change of the form of material substances through the media-assisted Discovery Learning model in science learning at SDN 8 Barru. This study aims to find out the concept of changing the form of media-assisted forms in the science learning process at SDN 8 Barru, Barru Regency. This type of research is classroom action research (PTK). The research instrument is the student worksheet (LKPD). The source of research data is the results of observations in the classroom, interviews from Natural Science teachers, and students. The results of the study showed that the improvement of understanding the changes in the form of physical substances using the 2d media-assisted discovey learning model obtained good and quite satisfactory results. So that it is in accordance with what is expected by the teacher. In the pre-action cycle, the percentage of students who completed was only 16% and the percentage of students who did not complete was 84%, based on the results of the learning evaluation carried out at the end of each meeting of cycles I and II, it showed that in cycle 1 with the percentage of students who completed 33% and the percentage of students who completed 67%, while in cycle II the percentage of students completed was 100%. Overall, the learning outcomes of students about the form of material substances have increased in each meeting. The implementation process uses the Discovery Learning model which contains effective learning concepts on media-assisted material changes in the form of objects in science learning. The impact of the material change of the form of this object provides a deep understanding and can distinguish the change of form through the media and experiments that are more fun, inspiring, and meaningful. In addition, students are inspired to experiment with the form of material substances in daily life.